Salivary micro RNA as a potential biomarker in oral potentially malignant disorders: A systematic review - T N Uma Maheswari; Archana Venugopal; Nivedhita Malli Sureshbabu; Prathiba Ramani (Tzu Chi Medical Journal)
Oral potentially malignant disorders (OPMD) are oral mucosal disorders which have a high potential to turn into malignancy. A recent report suggests that 16%–62% of epithelial dysplasia cases of OPMD undergo malignant transformation, showing the need for early detection of malignancy in these disorders. Micro RNA (miRNA) plays an important role in cellular growth, differentiation, apoptosis, and immune response, and hence, deregulation of miRNA is considered a signature of oral carcinogenesis. A search was done using MeSH terms in the PubMed, ScienceDirect databases, hand search, and finally, six studies were included in this systematic review. A total of 167 patients with oral cancer, 78 with OPMDs, 147 healthy controls, and 20 disease controls were analyzed for the expression of salivary miRNAs. Quality assessment based on the Quality Assessment of Diagnostic Accuracy Studies 2 tool was used to obtain a risk of bias chart using Revman 5.3 software and it was proved that the study done by Zahran et al. in 2015 had a low risk of bias. The results of this study revealed upregulated miRNA 184 with an area under the curve (AUC) of 0.86 and miRNA 21 with an AUC of 0.73 and downregulated miRNA 145 with an AUC of 0.68, which proved that these miRNAs are significant in detecting early malignancy in OPMD and should be further analyzed in various populations. This systematic review explored the potential of expression of salivary miRNA in OPMD for future studies. This could pave the way to utilize saliva as a surrogate marker in diagnosing early malignant changes in OPMD.